Estimation of Monthly Averaged Daily Solar Radiation with Sunshine Hours, Temperature, and Relative Humidity in Kathmandu, Nepal - Pant, B. P.; Budha, B.; Poudyal, K. N.; Acharya, B. (Journal of Nepal Physical Society, 2020)
This study is mainly concerned with the performance of various single and multiple meteorological parameter models to estimate the global solar radiation (GSR) on the horizontal site of Kathmandu, Nepal located at 27.69° N, 85.35° E at an altitude of 1338 meter from the sea level. The main concern of this research is to evaluate the preciseness and appropriateness of various models and to do that we have implemented diverse statistical tests. The results exhibit that all the used models have a good correlation for the determination of monthly averaged daily global solar radiation on the horizontal site of Kathmandu. Nonetheless, the sunshine hour and temperature-based model have shown a better agreement between the measured and estimated GSR of the studied site with RMSE and R2 values 0.88 and 0.87, respectively. The value of correlation coefficients a, b and c are found to be 0.42, 0.53, and 0.01, successively.